How does climate exacerbate root causes of conflict in Mali? Climate Security Pathway Analysis - Kurath, Tina; Madurga Lopez, Ignacio M.; Ferré Garcia, Tània; Dutta Gupta, Tanaya; Carneiro, Bia; Liebig, Theresa Ines; Läderach, Peter R.D.; Pacillo, Grazia (CGIAR System Organization, 2022)
This factsheet gives answers on how climate exacerbates root causes of conflict in Mali, using an impact pathway analysis. Two main impact pathways are identified: 1. Livelihood and Food Security: Climate variability and extreme weather events undermine the viability of climate-sensitive livelihoods dependent on natural resources such as livestock, agriculture, and fishery. While seasonal migration has been a frequent adaptation strategy, migration patterns are becoming more permanent, leading to increased competition in host communities. At the same time, livelihood insecurity has been a driver for recruitment into non-state armed groups, exacerbating conflict dynamics.; 2. Resource Availability and Access: Climate change and variability impact resource availability and environmental conditions, contributing to an increase in the competition over the access and use of natural resources, reducing levels of social cohesion, and increasing conflicts between and among different livelihood groups. Disputes for access and use of limited resource availability concerns mostly land and water sources, crucial for Mali’s agricultural sector.